Effects of Chromolaena odorata on mammalian biodiversity in Hluhluwe-iMfolozi Park, South Africa - Somers, Michael J. (University of Pretoria, 2013)
Dissertation (MSc (Wildlife Management))--University of Pretoria, 2009.